ADSORPTION AND DESORPTION OF DIFFERENT ORGANIC MATTER FRACTIONS ON IRON OXIDE - Gu B.; Schmitt J.; Chen Z.; Liang L.; McCarthy J.F. (My University, 1995)
Natural organic matter (NOM) is a complex mixture of different organic components (or fractions), yet few studies have examined the fractional adsorption of NOM on mineral surfaces. In this study, we fractionated NOM into hydrophobic (HbA) and hydrophilic (HL) subcomponents and two size fractions (with nominal molecular weights cut off at 3000 (3 K) dalton in an attempt to elucidate the adsorption and desorption mechanisms of NOM on iron oxide surfaces. Results indicated that, on a C weight basis, larger size HbA fraction was preferentially adsorbed (with a higher adsorption affinity and capacity) over smaller size HL fraction. However, on an O weight basis, less HbA fraction was adsorbed relative to the HL fraction, because HbA contained about 1.34 times more C but 0.82 times less O than the HL. These observations are consistent with results which indicate that only limited adsorption sites are available on the iron oxide surfaces and that the mechanism of HbA and HL adsorption was dominated by surface complexation-ligand exchange. FTIR and NMR spectroscopy and studies with several substituted benzoic acids/phenols further indicated that carboxyl and hydroxyl functional groups of these NOM fractions were actively involved in the reactions, and the steric arrangement of these functional groups may have played an important role in determining the adsorption of NOM fractions. Desorption studies indicated that the adsorbed NOM macromolecules on iron oxide surfaces were strongly bound at a given pH and ionic composition, resulting in a strong adsorption-desorption hysteresis. One possible explanation for the observed hysteresis is that the solution composition and equilibria are not identical between adsorption and desorption phases of the experiment because of preferential or selective adsorption of certain NOM fractions. This study implies that, due to the polydispersity of NOM, the competitive and fractional adsorption-desorption of NOM subcomponents must be considered in order to better predict NOM partitioning between the solution and solid phases and, therefore, the transport behavior of NOM in the subsurface soil environment.